PENGARUH TRANSFORMASI DIGITAL TERHADAP KINERJA USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI ERA EKONOMI DIGITAL - Hasan Husaini (PT Saha Kreasi Indonesia, 2026)
Digital transformation has become an essential element in improving the performance of Micro, Small, and Medium Enterprises (MSMEs) in the digital economy era. This study aims to analyze the impact of digital transformation on MSME performance, particularly in terms of revenue growth, operational efficiency, market expansion, and business competitiveness. The method used is a qualitative approach through a literature review of relevant scientific sources. The findings indicate that digital transformation has a significant positive impact on MSME performance, mainly through the utilization of digital platforms such as e-commerce, social media, and digital payment systems. Digitalization enables broader market access, cost efficiency, and faster business processes. However, the implementation of digital transformation still faces several challenges, including limited digital literacy, infrastructure constraints, and access to capital. Therefore, collaboration among government, business actors, and private sectors is needed to strengthen the MSME digital ecosystem sustainably.